2016
DOI: 10.1007/s13205-016-0558-8
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular characterization of phytoplasmas of ‘Clover proliferation’ group associated with three ornamental plant species in India

Abstract: Suspected phytoplasma symptoms of little leaf, yellowing, chlorosis, phyllody, witches’ broom, and stunting were observed on ten different ornamental plant species at New Delhi, Andhra Pradesh, Haryana, Bengaluru, and Pune, India, during March to July 2016. To investigate the possibility of phytoplasma etiology, PCR assays were performed using universal primer pairs (P1/P7 followed by 3Far/3Rev) specific to the phytoplasma 16Sr RNA gene. First round PCR amplification with primer pair P1/P7 did not yield expect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…Araucaria little leaf (Gupta et al 2009), brinjal little leaf (Azadvar and Baranwal 2012), Withania little leaf (Zaim and Samad 1995;Samad et al 2006), Portulaca little leaf (Samad et al 2008), Datura little leaf (Raj et al 2009;Singh et al 2012) and Calotropis gigantea leaf yellows (Madhupriya et al 2010). However, occurrence of 16SrVI-D subgroup phytoplasma was reported only on anantmool, lemongrass, sesame, Hibiscus rosa-sinensis, Saponaria officinalis and Allamanda cathartica (Madhupriya et al 2014(Madhupriya et al , 2015Khasa et al 2016). Hence, in our study, brinjal is reported to be an additional host of 'Ca.…”
Section: Discussionmentioning
confidence: 54%
“…Araucaria little leaf (Gupta et al 2009), brinjal little leaf (Azadvar and Baranwal 2012), Withania little leaf (Zaim and Samad 1995;Samad et al 2006), Portulaca little leaf (Samad et al 2008), Datura little leaf (Raj et al 2009;Singh et al 2012) and Calotropis gigantea leaf yellows (Madhupriya et al 2010). However, occurrence of 16SrVI-D subgroup phytoplasma was reported only on anantmool, lemongrass, sesame, Hibiscus rosa-sinensis, Saponaria officinalis and Allamanda cathartica (Madhupriya et al 2014(Madhupriya et al , 2015Khasa et al 2016). Hence, in our study, brinjal is reported to be an additional host of 'Ca.…”
Section: Discussionmentioning
confidence: 54%
“…The 16SrVI-D phytoplasma subgroup, have already been reported earlier as a major group of phytoplasma infecting several crops viz. brinjal (Rao and Kumar 2017), ornamental plants (Khasa et al 2016), medicinal plants (Madhupriya et al 2015) and sesame (Madhupriya et al 2015) in India.…”
Section: Discussionmentioning
confidence: 99%
“…In cucumber, phytoplasmas have been reported to be associated to disease, belonging to different groups (Montano et al 2006;Montano et al 2007). The phytoplasmas of 16SrVI clover proliferation (subgroup VI-A) have been reported to infect many plant species in the world (Khasa et al 2016;Zibadoost et al 2016;Choueiri et al 2007). However, there is no previous report of subgroup 16SrVI-A isolates infecting cucumber in Turkey.…”
Section: Discussionmentioning
confidence: 99%